Hermeneutic analysis as a basis of forming a musician’s artistic experience - Olena P. Burska, Natalia V. Liva, Tetiana D. Hrinchenko,Olena M. Yakymchu, Olena Y. Vereshchahina-Biliavska, (Opción, 2020)
In the course of the work, it has been found that hermeneutical analysis of music is the most complex kind of artistic reality analysis. Interpretation as a result of hermeneutical analysis becomes a necessary condition for the formation of artistic experience. The basic procedure of hermeneutical methods of communication with works of art is the use of the performer in the author’s spiritual world, the subjective empathy and objective reconstruction of the cultural and historical world. All of the suggested above allows come to statement that mastering hermeneutical analysis skills is the basis for shaping the artist’s artistic experience.